Functional imaging in microfluidic chambers reveals sensory neuron sensitivity is differentially regulated between neuronal regions. Issue 7 (July 2018) - Clark, Alex J.; Menendez, Guillermo; AlQatari, Mona; Patel, Niral; Arstad, Erik; Schiavo, Giampietro; Koltzenburg, Martin
Abstract : Abstract: Primary afferent sensory neurons are incredibly long cells, often traversing distances of over 1 m in humans. Cutaneous sensory stimuli are transduced in the periphery by specialised end organs or free nerve endings, which code the stimulus into electrical action potentials that propagate towards the central nervous system. Despite significant advances in our knowledge of sensory neuron physiology and ion channel expression, many commonly used techniques fail to accurately model the primary afferent neuron in its entirety. In vitro experiments often focus on the cell somata and neglect the fundamental processes of peripheral stimulus transduction and action potential propagation. Despite this, these experiments are commonly used as a model for cellular investigations of the receptive terminals. We demonstrate that ratiometric calcium imaging performed in compartmentalised sensory neuron cultures can be used to directly and accurately compare the sensitivity and functional protein expression of isolated neuronal regions in vitro. Using microfluidic chambers, we demonstrate that the nerve terminals of cultured dorsal root ganglion neurons can be depolarised to induce action potential propagation, which has both tetrodotoxin-resistant and tetrodotoxin-sensitive components. Furthermore, we show that there is a differential regulation of proton sensitivity between the sensory terminals and somata in cultured sensory neurons. We also demonstrate that capsaicin sensitivity is highly dependent on embryonic dissection age. This approach enables a comprehensive method to study the excitability and regional sensitivity of cultured sensory neurons on a single-cell level. Examination of the sensory terminals is crucial to further understand the properties and diversity of dorsal root ganglion sensory neurons. Abstract : The differential sensitivity of soma, axon, and terminals of primary nociceptors to pain-producing substances and analgesic drugs can be studied in microfluidic compartmentalised cultures.Supplemental Digital Content is Available in the Text.